A resource to empirically establish drug exposure records directly from untargeted metabolomics data - Zhao, Haoqi Nina; Kvitne, Kine Eide; Brungs, Corinna; Mohan, Siddharth; Charron-Lamoureux, Vincent; Bittremieux, Wout; Tang, Runbang; Schmid, Robin; Lamichhane, Santosh; Xing, Shipei; El Abiead, Yasin; Andalibi, Mohammadsobhan S; et al. (Nature communications, 2025)
Despite extensive efforts, extracting medication exposure information from clinical records remains challenging. To complement this approach, here we show the Global Natural Product Social Molecular Networking (GNPS) Drug Library, a tandem mass spectrometry (MS/MS) based resource designed for drug screening with untargeted metabolomics. This resource integrates MS/MS references of drugs and their metabolites/analogs with standardized vocabularies on their exposure sources, pharmacologic classes, therapeutic indications, and mechanisms of action. It enables direct analysis of drug exposure and metabolism from untargeted metabolomics data, supporting flexible summarization at multiple ontology levels to align with different research goals. We demonstrate its application by stratifying participants in a human immunodeficiency virus (HIV) cohort based on detected drug exposures. We uncover drug-associated alterations in microbiota-derived N-acyl lipids that are not captured when stratifying by self-reported medication use. Overall, GNPS Drug Library provides a scalable resource for empirical drug screening in clinical, nutritional, environmental, and other research disciplines, facilitating insights into the ecological and health consequences of drug exposures. While not intended for immediate clinical decision-making, it supports data-driven exploration of drug exposures where traditional records are limited or unreliable.
Keywords: Humans; lidé; Tandem Mass Spectrometry; HIV infekce; tandemová hmotnostní spektrometrie; Metabolomics; HIV Infections; metabolomika